AB0541 Relationship Between Ultrasonographic Salivary Glands Abnormalities and Subclinical Cardiovascular Involvement in Patients with Primary SjÖgren Syndrome. (9th June 2015) - Batticciotto, A.; Rigamonti, F.; Atzeni, F.; Antivalle, M.; Boccassini, L.; Gianturco, L.; Battellino, M.; Talotta, R.; Turiel, M.; Doria, A.; Sarzi-Puttini, P.
Abstract : Background: Different studies showed that systemic inflammation, elevated levels of inflammatory cytokines, and immune dysregulation, typical of the inflammatory autoimmune disease, play a role in accelerated atherosclerosis. However, only few studies showed sub-clinical cardiovascular (CV) involvement in patients with primary Sjögren's syndrome (pSS) (1). Moreover, it has been demonstrated that salivary glands ultrasound (US) score is strictly related to the histological inflammatory abnormalities. Objectives: The primary aim of our study was to investigated sub-clinical cardiovascular involvement in pSS patients by means of asymmetric dimethylarginine (ADMA) serum levels, coronary flow reserve (CFR), intima-media thickness (cIMT) and pulse wave velocity (PWV). The secondary aim was to performed salivary glands US and to compare these findings with cardiovascular parameters. Methods: Fifty-three consecutive outpatients with pSS (7 M, 46 F; mean age 59.8 range 43-80 yrs; mean disease duration of 59.5 range 6-156 months) without classical CV risk factors and/or known CV diseases, and 22 homogenous healthy controls were enrolled. RF-QIMT and RF-QAS technologies were used to assess IMT and PWV and Dipyridamole transthoracic stress echocardiography to obtain CFR. Plasma ADMA levels, inflammatory markers and autoantibodies were also evaluated. My Lab 70 (Esaote, Florence, Italy) with linear probe (6-18 MHZ) was used to assess salivary glands US according to the scoring system published by Salaffi et al. (2). Results: Although within the normal range, CFR in pSS patients was lower than that of the controls (2.6±0.23 vs 3.2±0.32 p<0.0001), whereas PWV and ADMA levels were significantly higher (9.2±1, 8m/s vs 6.8±0.9m/s p<0.0001 and 0.76±0.07μM vs 0.54±0.05μM p<0.0001). Although QIMT values were not different in the two groups, the percentage of pSS patients with pathological values was higher (47/53 vs 12/22 p=0.001). Moreover, a significant correlation between salivary glands US score BMI (p=0.001), CRP (p=0.034) and ANA (p<0.0001) was found. However, no correlation between sub-clinical CV index was found (PWV r=-0.205 p=0.140, Q-IMT r=0.261 p=0, 06, CRF r=-0.194 p=0.249, ADMA r=0.249 p=0.075). Conclusions: Although CFR values were normal, higher ADMA levels, PWV values and percentage of subjects with pathological Q-IMT compared to healthy controls suggest that pSS patients without classical CV risk factors have an early endothelial dysfunction and sub-clinical atherosclerosis. However, no correlation between salivary US score and the sub-clinical CV involvement parameters was found. References: Atzeni F, Sarzi-Puttini P, Signorello MC, Gianturco L, Stella D, Boccassini L, Ricci C, Bodini BD, Batticciotto A, De Gennaro-Colonna V, Drago L, Turiel M. New parameters for identifying subclinical atherosclerosis in patients withprimary Sjögren's syndrome: a pilot study. Clin Exp Rheumatol. 2014;32(3):361-8. Salaffi F, Argalia G, Carotti M, Giannini FB, Palombi C. Salivary gland ultrasonography in the evaluation of primary Sjögren's syndrome. Comparison with minor salivary gland biopsy. J Rheumatol 2000;27:1229–36. Disclosure of Interest: None declared